2010
DOI: 10.4315/0362-028x-73.8.1552
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks Where Food Workers Have Been Implicated in the Spread of Foodborne Disease. Part 7. Barriers To Reduce Contamination of Food by Workers

Abstract: Contamination of food and individuals by food workers has been identified as an important contributing factor during foodborne illness investigations. Physical and chemical barriers to prevent microbial contamination of food are hurdles that block or reduce the transfer of pathogens to the food surface from the hands of a food worker, from other foods, or from the environment. In food service operations, direct contact of food by hands should be prevented by the use of barriers, especially when gloves are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 67 publications
0
77
0
4
Order By: Relevance
“…Altekruse et al (1998) identified 32 cheese-associated outbreaks in the United States, 11 attributed to contamination at the farm, during the manufacture or during processing (before distribution), and 2 among them were associated with eating mozzarella cheese (1 improper pasteurization, 1 post-pasteurization contamination). According to Todd et al (2010), several foodborne outbreak investigation reports have identified the hands of food workers as the source of pathogens in the implicated food. Among them a Center for Disease Control and Prevention (2006) weekly report which reported that during August-September 2005 a total of 52 (2.44%) of 2,160 inmates at a state correctional facility reported diarrhea, including 17 (33%) with bloody diarrhea.…”
Section: Resultsmentioning
confidence: 99%
“…Altekruse et al (1998) identified 32 cheese-associated outbreaks in the United States, 11 attributed to contamination at the farm, during the manufacture or during processing (before distribution), and 2 among them were associated with eating mozzarella cheese (1 improper pasteurization, 1 post-pasteurization contamination). According to Todd et al (2010), several foodborne outbreak investigation reports have identified the hands of food workers as the source of pathogens in the implicated food. Among them a Center for Disease Control and Prevention (2006) weekly report which reported that during August-September 2005 a total of 52 (2.44%) of 2,160 inmates at a state correctional facility reported diarrhea, including 17 (33%) with bloody diarrhea.…”
Section: Resultsmentioning
confidence: 99%
“…Corroborating with this, Phang & Bruhn (2011), also found in their study that the hands of the food handlers were the vehicle with the highest possibilities for cross contamination during the work routine. This may be justified by the fact that the contamination of the hands of food handlers is one of the factors found by studies to make the greatest contribution to foodborne disease outbreaks (Todd et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Microbes are present on all the surfaces of the hand, particularly in high concentration under the nails. 32,33 Around 61% children all over Mumbai had visible dirt in their finger nails and 39% had grown nails at the time of interview. For effective rubbing of all the surfaces of hands, particularly the nails and space between the fingers for at least 20 seconds is recommended which were found to be practiced by very small percentage of children.…”
Section: Discussionmentioning
confidence: 99%